Impact of food and beverage management on customer satisfaction in the hospitality sector: A case study of White Horse Inn Hotel, Kabale District - Tumusiime, Cosmas Bwambale (Kabale University, 2025)
Researching on customer satisfaction is important because satisfied customers become loyal customers. Therefore, it is crucial to measure customer satisfaction towards food and beverage management because satisfied customers make repetitive purchasing and recommendations to others that will make profits of that particular hospitality establishment. Customer satisfaction with food and beverage management can significantly be influenced by food and beverage presentation, image and physical environment. Hence, earlier, many studies have shown the relationship between food and beverage management and customer satisfaction. But still, limited literature has been focused on the impact of the confirmation of customer expectation on the relationship between food and beverage management and customer satisfaction. Hence, this study aims to measure customer satisfaction based on the food and beverage presentation, image and physical environment. A total of 200 questionnaires were distributed to customers and staff at White Horse Inn Hotel in Kabale district . Totally 133 questionnaires were used for further analysis out of 200, representing a response rate of 66.5%. The result of the study revealed that food and beverage presentation has a significant and positive relationship with confirmation of customers’ expectations and in turn, their satisfaction level towards food and beverage management. Implications and directions for future research are also highlighted in this present study.